Activité antioxydante de quelques plantes utilisées dans la région de Tiassalé (Côte d’Ivoire) dans le maintien de la santé de la peau - Georges, Koffi Akessé; Constant, Ahoua Angora Remi; Lynda, Ekou; Tchirioua, Ekou; Witabouna, Kone Mamidou (European Scientific Journal, ESJ, 2018)
Skin health is a concern for many people. This aim of this study is to evaluate in vitro the antioxidant activity of 10 plants used in cosmetopoeia for the maintenance of skin health. To achieve this objective, 30 extracts were tested using 2,2’-diphenyl-1-picrylhydrazyl radical (DPPH) and 2,2’-azino-bis (3-ethylbenzothiazoline-6) acid. -sulfonic) (ABTS + •) assays. The extracts studied were rich in total polyphenols, flavonoids, gallic tannins and alkaloids. For the DPPH reduction, 7 extracts including 5 methanolic and 2 aqueous extracts showed a percentage of inhibition similar to that of Vitamin C (95.79 ± 10.53%) used as a control. With ABTS, 11 extracts (5 methanol, 3 aqueous and 3 hexane) gave reduction percentages close to Trolox (95.97 ± 8.51%). These active plants could play a role in the maintaining of skin.